2008
DOI: 10.1007/s00280-008-0694-x
|View full text |Cite
|
Sign up to set email alerts
|

Topotecan distribution in an anephric infant with therapy resistant bilateral Wilms tumor with a novel germline WT1 gene mutation

Abstract: The therapeutic strategy for bilateral Wilms tumor (WT) remains a challenge. Especially in cases with chemotherapy resistant disease, bilateral nephrectomy is sometimes inevitable. For optimal cure rates stage V WT patients beneWt from adjuvant treatment; however, there are limited data available on chemotherapy pharmacokinetics in anephric children. In this report, we describe a 10-month old girl with bilateral Wilms tumor and a novel germline WT1 gene mutation. This patient hardly showed any response on preo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
(55 reference statements)
0
4
0
2
Order By: Relevance
“…The fifth patient suffered from local relapse in the pelvic region and had a second relapse after topotecan treatment and died of disease. Since in one case, topotecan was given as adjuvant chemotherapy during peritoneal dialysis, it seems feasible to administer topotecan to anephric patients [26]. Topotecan clearance turned out to be minimally affected by hemodialysis and was similar to that observed in children without renal failure [26,29].…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The fifth patient suffered from local relapse in the pelvic region and had a second relapse after topotecan treatment and died of disease. Since in one case, topotecan was given as adjuvant chemotherapy during peritoneal dialysis, it seems feasible to administer topotecan to anephric patients [26]. Topotecan clearance turned out to be minimally affected by hemodialysis and was similar to that observed in children without renal failure [26,29].…”
Section: Discussionmentioning
confidence: 63%
“…In two patients, the tumour showed initial temporary response to topotecan, however, becoming progressive during treatment (patient 12 and 28, Table ). In one other patient, response could not be measured, since topotecan was given as adjuvant therapy (with dialysis driven pharmacological excretion) after surgery (sequential nephrectomy in a non‐chemoresponse IR patient with bilateral WT) (patient 19, Table ) . Four patients showed stable disease during topotecan treatment and had surgery thereafter.…”
Section: Resultsmentioning
confidence: 99%
“…После внутривенного введения кривая снижения концентрации топотекана в плазме крови носит биэкспоненциальный характер. Последние фармакокинетические исследования у пациентов с нарушением функции почек показали, что снижение дозы топотекана с 1,5 до 0,75 мг/м 2 приводит к адекватной концентрации препарата в плазме и не препятствует его элиминации, что делает возможным его использование в качестве адьювантной химиотерапии у больных, находящихся на заместительной почечной терапии [2,5] При нормальной функции почек AUC выше у пациента, получившего бóльшую дозу лекарственного препарата, в то время как при введении одинаковых доз препарата бóльшая AUC получена у пациентов с нарушенной функцией почек. Таким образом, при расчете дозы химиопрепарата по формуле Калверта осуществляется индивидуальный подбор дозировки, оптимальной для конкретного больного в зависимости от фармакокинетики и процента выведения через мембрану диализата [6].…”
Section: Discussionunclassified
“…При прогрессирующем или нерезонансном заболевании двусторонняя нефрэктомия становится неизбежной. Применение адъювантной химиотерапии у анефрированных детей изучено недостаточно, что иллюстрируется наличием скудной информации о коррекции дозы различных цитостатических препаратов при заместительной почечной терапии у данной категории пациентов [2].…”
Section: вклад авторовunclassified
“…In the past, various research studies have shown a relationship with the factors that contributed to tumor development which are related to mother's hormonal and father's occupational factors [4] . The average presentation at age concerned to one side is 42-47 months, whereas its presents on either side at the average age of 30-33 months [10] .…”
Section: Introductionmentioning
confidence: 99%